1996
DOI: 10.1002/masy.19961080117
|View full text |Cite
|
Sign up to set email alerts
|

The application of hydrated mineral fillers as fire retardant and smoke suppressing additives for polymers

Abstract: The characteristics of hydrated mineral fillers are discussed with reference to their use as fire retardant additives for polymers. Particular consideration is given to their mode of action and criteria which influence their performance, both in reducing polymer flammability and in suppressing smoke evolution during combustion. Methods for reducing their adverse effect on mechanical properties of the host polymer are also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…MH provides effective flame retarding effects by heat absorption and formation insulating protective char layer . Wang et al found that MH could decrease smoke yield of LLDPE by the examination of cone calorimeter tests and previously Hornsby et al found the similar results and convinced that the generated magnesium oxide catalyzed the oxidation of carbon to CO and CO 2 , resulting in smoke reduction. However, the yields of CO and CO 2 at different temperature should be further verified.…”
Section: Introductionmentioning
confidence: 72%
“…MH provides effective flame retarding effects by heat absorption and formation insulating protective char layer . Wang et al found that MH could decrease smoke yield of LLDPE by the examination of cone calorimeter tests and previously Hornsby et al found the similar results and convinced that the generated magnesium oxide catalyzed the oxidation of carbon to CO and CO 2 , resulting in smoke reduction. However, the yields of CO and CO 2 at different temperature should be further verified.…”
Section: Introductionmentioning
confidence: 72%
“…PF and MDI provided a better yield of char at about 24.88 and 20.61 wt%, respectively, at 850°C. This showed that theirthermal behavior was better than that of UF (5.40 wt%) or MUF (6.99 wt%), as the proposed action mechanism is based on the charred layer acting as a physical barrier, which slows down heat, and results in mass transfers between the gas and condensation phases (Camino et al, 1993, Hornsby, 1996and Zhu & Shi, 2001). Figure 5 shows the Infrared spectrometric (IR) response of the four types of adhesives in the TGA-IR measurements.…”
Section: Thermal Decomposition Of Various Adhesivesmentioning
confidence: 99%
“…They also have an added benefit of leaving behind a protective microporous layer of the metal oxide after dehydration. Hornsby [1] neatly summarizes the FR properties of hydrated mineral fillers and also briefly explores their compatibility in polymeric systems.…”
Section: Introductionmentioning
confidence: 99%